Family violence, one step to feminicide - Contreras Cuzcano, Jhonny Hans (2019)
Societies like ours are currently struggling in a structural crisis of different kinds, which seriously affects peaceful coexistence. One of these factors lies on family violence cases, which, despite the efforts of the international community and the Peruvian State itself, are increased geometrically and, what is worse, it does not end there, but almost all these cases of domestic violence end in «feminicide». These facts that determine a univocal connection between family violence and feminicide require, besides laws, a comprehensive and multidisciplinary treatment of effective protection when domestic violence is denounced, such as campaigns and mental health treatment, as well as reaffirming and strengthening the family in the raising of children in values, complementing it with an integral formative work since the first years in public and private schools.